Being Fair about the Design of FAIR Data Standards - Bezuidenhout, Louise (My University, 2020)
Since 2014 the FAIR data movement has been rapidly altering the landscape of data sharing and re-use. Support for the FAIR 3 movement has seen the evolution of disciplinary-specific standards to foster data that are “finable, accessible, interoperable 4 and reusable.” While these exciting developments should not be minimised, it is important to interrogate how these standards 5 are set. Key questions to ask include how representation in standard setting communities is addressed; what infrastructures 6 and resources these emergent standards are reliant on; and how standards dictate specific interpretations of “value” and 7 “valuable data.” Asking such questions introduces a needed reflexivity into FAIR discussions, as standard setters interrogate 8 what data practices commit present—and future—researchers to.
Keywords: Open Data; FAIR; low/middle-income countries